Early viral‐specific T‐cell testing predicts late cytomegalovirus reactivation following liver transplantation. Issue 5 (19th June 2018) - Sood, S.; Haifer, C.; Yu, L.; Pavlovic, J.; Gow, P.J.; Jones, R.M.; Visvanathan, K.; Angus, P.W.; Testro, A.G.
Abstract: Introduction: Although antiviral prophylaxis is effective in preventing early cytomegalovirus (CMV) reactivation following liver transplantation (OLT), it predisposes patients to late CMV after prophylaxis has ceased. QuantiFERON–CMV (QFN‐CMV, Qiagen, The Netherlands) measures an individual's viral‐specific immune response. Methods: Fifty‐nine OLT recipients were prospectively monitored post‐OLT in an observational cohort study. QFN‐CMV was performed at regular time‐points. An absolute QFN‐CMV <0.1 IU/mL was considered non‐reactive. Results: 50/59 (84.7%) had a reactive QFN‐CMV by M6. 38/59 (64.4%) had antiviral prophylaxis or treatment before M6, with 31/38 (81.6%) developing a reactive QFN‐CMV by 6 months. Over 90% already had a reactive result as early as 3 months post transplant, 3 patients (5.08%) developed late CMV between 6‐12 months (median 251 days)—all had a non‐reactive M6 QFN‐CMV. And 2/3 experienced CMV disease. Non‐reactive M6 QFN‐CMV was significantly associated with late CMV (OR = 54.4, PPV = 0.33, NPV = 1.00, P = .003). Conclusion: Although only 5% of recipients developed late CMV, 2/3 suffered CMV disease. M6 QFN‐CMV has an excellent NPV for late CMV, suggesting patients who exhibit a robust ex vivo immune response at M6 can safely cease CMV monitoring. Furthermore, >90% already express viral‐specific immunity as early as 3 months. Conceivably, antiviral prophylaxis could be discontinued early in these patients.